Network and Margin: The Case of Chili Supply Chain in Bekasi Regency - Johan Krisnanto Runtuk; Nurhayati Surbakti (JIE Scientific Journal on Research and Application of Industrial System, 2019)
Chili (cabai rawit) is one commodity that is very significant for people's daily consumption. However, the price of chili often experiences a significant increase. This condition will make the sales of chili decrease dramatically if the price rises. In addition, the margins felt by farmers to sellers of chili in the traditional market are uneven. this is also felt by other vegetable sellers. This research aims to identify the supply chain network of chili in Bekasi Regency. The margin of each stage in the supply chain network is also identified. This research employs descriptive analytical. Descriptive analytics is a preliminary stage of data processing that creates a summary of historical data to yield useful information and possibly prepare the data for further analysis. Data collection method used is by direct observation in Bekasi regency and other locations associated with suppliers of chili, then we employ direct and a phone interview with respondents. The finding shows that there are three main stages in supply chain of chili in Bekasi Regency, namely producer, distributor and consumer. The consumers can buy the product from three channels, that shows the flows of product from producer to consumer. The share of margin in the producer stage for the second flow is lower than the first flow, with the value 56.25% from 75%, then, the third flow is higher than the second flow but still lower than the first flow, with the value 64.29%.